Proportion and reasons for loss to follow-up in a cohort study of people who inject drugs to measure HIV and HCV incidence in Kerman, Iran - Ghazal Mousavian; Nima Ghalekhani; Fatemeh Tavakoli; Willi McFarland; Armita Shahesmaeili; Heidar Sharafi; Mehrdad Khezri; Soheil Mehmandoost; Jasem Zarei; Hamid Sharifi; Ali Mirzazadeh (BMC, 2021)
Abstract Background Understanding the reasons for loss to follow-up (LTFU) in cohort studies, especially among marginalized groups such as people who inject drugs (PWID), is needed to strengthen the rigor of efficacy trials for prevention and treatment interventions. We assessed the proportion and reasons for loss to follow-up in a recent cohort of PWID enrolled in the southeast of Iran. Methods Using respondent-driven sampling, we recruited 98 PWID age 18 years or older who reported injecting drugs in the past 6 months, and were negative for HIV and HCV at initial screening. Participants were followed at 6 week intervals, alternating a short six-week visit and long 12-week or quarterly visit to measure incidence of HIV and HCV. Methods to enhance retention included incentives for completing each visit, tracking people who missed the scheduled visits through their peer referral networks, engaged outreach teams to explore hotspots and residences, and photos. LTFU was defined as participants who missed their quarterly visits for two or more weeks. Results Mean (SD) age of participants was 39.7 years (SD 9.6). Of 98 enrolled, 50 participants (51.0%) were LTFU by missed their scheduled quarterly visits for 2 weeks or more. For those whose reasons for LTFU could be defined (46.0%, 23 of 50), main reasons were: forgetting the date of visit (43.5%, 10 of 23), being incarcerated (39.1%, 9 of 23), and moving out of the city (17.4%, 4 of 23). Conclusion This study highlighted the difficulty in retaining PWID in longitudinal studies. Despite having several retention strategies in place, over half of PWID were LTFU. The LTFU might be reduced by setting up more effective reminder systems, working closely with security systems, and online means to reach those who move outside the study area.